AR Application Design for SV IPB Software Engineering Technology Study Program using Design Thinking Method - Dhila Aprilianti (Batrisya Education, 2024)
The application of Augmented Reality (AR) is steadily increasing in the development of modern applications, which combines virtual elements with the real world to provide an immersive user experience. AR applications are crucial to the IPB Software Engineering Technology Study Program. Design Thinking methods ensure a thorough understanding of user needs and drive innovative solutions. The design thinking method is used to design AR applications with a focus on user experiences and interactive multimedia. Design processes include learning user experiences, gathering ideas, making prototypes, and then performing application testing and evaluation. The aim of this research is to create AR applications that meet user requirements and have interesting and meaningful interactive media features. The results of this production and research will also contribute to the development of the IPB Software Engineering Technology study program.